Sleep duration, sleep quality, body mass index, and waist circumference among young adults from 24 Low- and Middle-income and Two high-Income countries - Peltzer, Karl; Pengpid, Supa (International journal of Environmental research and public health, 2017)
Obesity and its comorbidities have emerged as a leading public health concern. The aim of this study was to explore the relationship between body mass index (BMI), waist circumference (WC) and sleep patterns, including duration and disturbances. A cross-sectional questionnaire survey and anthropometric measurements were conducted with undergraduate university students that were randomly recruited in 26 universities in 24 low- and middle-income and two high-income countries. The sample included 18,211 (42.1% male and 57.9% female, mean age 21.0 in male and 20.7 years in female students) undergraduate university students. The overall BMI was a mean of 22.5 kg/m2 for men and 22.0 kg/m2 for women, and the mean WC was 78.4 cm for men and 73.8 cm for women. More than 39% of the students reported short sleep duration (≤6 h/day) and over 30% reported moderate to extreme sleep problems. In a linear multivariable regression, adjusted for sociodemographic and lifestyle factors, short sleep duration was positively associated with BMI in both men and women, and was positively associated with WC among women but not among men. SleepqualityorproblemsamongmenwerenotassociatedwithBMI,whileamongwomenmildsleep problems were inversely associated with BMI, and poor sleep quality or problems were positively associatedwithWCbothamongmenandwomen. Thestudyconﬁrmedanassociationbetweenshort sleep duration and increased BMI and, among women, increased WC, and an association between poor sleep quality and increased WC but not BMI. Further, differences in the association between sleep characteristics and BMI and WC were found by region and country income
International Journal of Environmental Research and Public Health (2017) 14, 566
Keywords: Sleep duration; Sleep quality; Body mass index; Waist circumference; Young adults; Low- and middle-income countries; Obesity; Interpersonal relation in young adults